Long-Term Outcomes of Allogeneic Ocular Surface Reconstruction: Keratolimbal Allograft (KLAL) Followed by Penetrating Keratoplasty (PK) - Katarzyna Krysik; Dariusz Dobrowolski; Dorota Tarnawska; Edward Wylegala; Anita Lyssek-Boroń (Journal of Ophthalmology)
Purpose. Long-term results of the patients with total LSCD, who had undergone keratolimbal allograft (KLAL) for limbal reconstruction followed by penetrating keratoplasty (PK). Methods. The study analyzes surgical treatment of 43 eyes with severe ocular surface disorders. All subjects underwent KLAL to achieve suitable conditions for consecutive PK. Due to failures of primary treatment in 17 eyes (39%), the KLAL was repeated. PK was performed in all the patients at 9-12 months after KLAL. As a retrospective study we analyzed data from the medical records including the preoperative and postoperative best corrected visual acuity, corneal clarity, surgical outcomes and complications, postoperative intraocular pressure, graft rejection, and other comorbidities and complications. Results. The preoperative visual acuity ranged from light perception to 0.01. The final improvement of visual acuity within a gain of one or more lines with the Snellen chart, including the results of successive surgical treatments after PK, was achieved in 23 operated eyes (53%). Early graft rejection was observed in 4 eyes (9%). In 3 eyes, it was manifested as endothelial rejection, and in 1 eye, as combined endothelial and epithelial rejection. PK failure requiring repetitive PK was present in 14 eyes (32%). Phthisis bulbi developed in 6 eyes (14%). Glaucoma or ocular hypertension was reported in 25 eyes (58%). A majority were treated with up to 3 topical agents or referred for trabeculectomy in 3 cases, transscleral cyclophotocoagulation in 2 eyes, and EX-PRESS glaucoma shunt implantation in 3 cases. Conclusions. Successful KLAL carries a high risk of subsequent PK failure. Visual function remains the second aim of treatment; the primary one is to stabilize the surface.